Hubungan antara Karakteristik Ekonomi dan Demografi terhadap Status Kebahagiaan Penduduk DKI Jakarta Tahun 2012 - Alfatihah Reno Maulani; Elwindra Elwindra (STIKes Persada Husada Indonesia, 2014)
The study of happiness has been widely applied as an indicatorofwelfare. In 2007, Bhutan became thefirst country to measure Gross National Happiness Index. Furthermore, there were some internationalorganizations that try to measure this index in several countries to learnabout the comparability, for example, The New Economics Foundation with The Happy Planet Index (HPI), The Organization for EconomicCooperation and Development (OECD) with Your Better Life Index (YBLI), and the Legatum Institute withProsperity Index (PI). Statistics Indonesia (BPS) conducted a national survey to measurelevel of Happiness in2013. Previously, preliminary survey was conducted in Jakarta in 2012. This study uses secondary data from the National Socioeconomic Survey (SUSENAS) Jakarta Year 2012 with atotal of 1,198 respondents. Chi squareanalysis was used to identify if there are difference in Economic and Demographic Characteristics (place oforigin, gender, age group, educational background, marital status, number of household members, and monthly average household expenditure) to the status of individual happiness (variable with 4 Likert scale, in the range 1 (Not Happy) to 4 (Very Happy). The results showed a tendency of higher happinessin the population of Kabupaten Kepualauan Seribu, female, in the age group of 17-24 years old, highly educated, married, a large number of household members, and have high average household expenditure per month.